2021
DOI: 10.1055/s-0041-1733880
|View full text |Cite
|
Sign up to set email alerts
|

Is MRI Overutilized for Evaluation of Knee Pain in Veterans?

Abstract: MRI is an essential diagnostic imaging modality for many knee conditions; however, it is not indicated in the setting of advanced knee arthritis. Inappropriate MRI imaging adds to health care costs and may delay definitive management for many patients. The primary purpose of this study was to ascertain the frequency of inappropriate MRI scans performed at one Veterans' Administration Medical Center (VAMC). We performed a retrospective chart review of all knee MRIs ordered over a 6-month period. Inappropriate M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The financial burden of a stress radiograph is much lower than that of a knee MRI. 3,25 It has been reported that the out-of-pocket cost of a knee MRI ranges from $459 to $2042 in the United States, 15,25 while the average cost of a 3-view knee radiograph is $282 (in 2021). 3 The difference in cost between stress radiographs and MRI for assessing anterior knee laxity is substantial for patients and the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…The financial burden of a stress radiograph is much lower than that of a knee MRI. 3,25 It has been reported that the out-of-pocket cost of a knee MRI ranges from $459 to $2042 in the United States, 15,25 while the average cost of a 3-view knee radiograph is $282 (in 2021). 3 The difference in cost between stress radiographs and MRI for assessing anterior knee laxity is substantial for patients and the health care system.…”
Section: Discussionmentioning
confidence: 99%